Ecological correlates of territory and home range size in North American dabbling ducks - Nudds, Thomas D; Ankney, Davison (Wildfowl, 1982)
A review of published, quantitative data suggested that the sizes of areas used by breeding Anas spp. is related to both body-size and resource dispersion. McKinney's hypothesis did not distinguish the separate contributions of each of those factors. The variability in social systems among dabbling ducks is correlated with the spatial and temporal variability of breeding habitats; social systems can be arranged along a continuum with 'rigid' territoriality common in stable habitats, but 'loose' territoriality and home-ranges prevailing in variable habitats.